Optimization studies on Biosorption of Copper (II) by Crab Shell Using Response Surface Methodology(RSM) - s, Sudesh (The Berkeley Electronic Press, 2010)
In the present work, crab shell was used as the biosorbent to remove copper from aqueous solution. Batch experiments were performed at different initial copper concentration of copper solutions (1-40 g/l), initial pH (2-9), temperature (20-400C), and biosorbent dosages (2-10 g/l). The maximum removal of copper using crab shell occurred at a pH of 3 and at a temperature of 400C using an optimum biosorbent dosage of 5 g/l. A mathematical model was proposed to identify the effects of the individual interactions of these variables on the biosorption of copper. The results have been modeled using response surface methodology using a Box-Behnken design. The response surface method was developed using three levels (-1, 0, +1) with the above mentioned four factors. The second order quadratic regression model fitted the experimental data with Prob > F to be < 0.0001. The experimental values were found to be in good agreement with the predicted values, with a satisfactory correlation coefficient of R2 = 0.9999.